Stratification on Aerial Photographs Improves Timber Estimates - Tiwari, K. P. (Indian Forester, 1977)
An investigation to assess the suitability of sampling design for timber eatimates by volume, basal area and tree count was made with systematic sampling with interpenetrating sampling units, regression method of estimation and stratified sampling with stratification done on black and white panchromatic serial photographs on 1 : 10,000 scale. It was found that last one gave most precise results. The S.E. % of stratified sampling was nearly half of that of the other two sampling Aerial photographs thus provide an unique opportunity of atratification to improve timber estimates.